Analysis of truncated growth hormone receptor 1 in the differential growth of fine flounder Paralichthys adspersus - Marín, Alan (2023)
Differences in body size within a fish population are a recurring problem in aquaculture. In fish farms, a higher growth rate is one of the most important selection traits, so growth dispersion with smaller batch sizes leads to increased production costs. Despite the importance of this dispersion in growth, the understanding of the molecular basis of these differences is still largely unknown. In the present work, we firstly determined that in the fine flounder Paralichthys adspersus the variant of the growth hormone receptor 1 (ghr1tr) is in agreement with a transcript truncation product of an alternative polyadenylation signal (APAs) embedded in an intronic region of ghr1 full length nucleotide sequence. Additionally, we observed that this region possesses a high identity with homologous regions in other Pleuronectiformes with documented differences in body size. Finally, our quantitative expression analysis, focusing on liver and muscle tissues, reveals that ghr1tr of P. adspersus was less expressed in bigger adult individuals. In this sense, this study proposes ghr1tr as the modulator of size dimorphism growth and that it could be a useful target for genetic studies on fine flounder breeding improvement.